ANALISIS PEREKRUTAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA INDUSTRI KREATIF AGENSI PERIKLANAN: (Studi Kasus Pada Sojourner Creative Agency Medan) - Furqan, Said; Siregar, Onan Marakali (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
To obtain good quality employees, organizations need to pay attention to the recruitment and development process, because from recruitment, competent employees will be found or in accordance with the criteria determined by the company, employee development is carried out so that employee knowledge can increase and with employee development can help realize the goals of the company. The purpose of this study is to analyze how the recruitment program is implemented by Sojourner Creative Agency and to analyze how the steps of developing human resources are to improve employee performance at Sojourner Creative Agency. This study collects information from interviewing informants consisting of key informants, main informants and additional informants. The data analysis technique uses the data reduction process, data presentation and discussion. The results of this study show that in the recruitment process carried out by Sojourner Creative Agency has been well pursued, companies recruit employees by looking at the abilities and potential of employees in the field of videography and photography, in the process of developing employees the company develops in terms of providing motivation, self-development, and developing employee skills, employees are also supervised and evaluated in every job done and this can help in the process of improving employee performance.